ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH PROVINSI ACEH PERIODE 2015-2019 - Adnan Bensaadi; Myra Salsabila (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
Motor vehicle tax (PKB) and Motor Vehicle Transfer Fee (BBNKB) are two components of Aceh's tax that have the potential to increase Aceh’s local own revenues. This research aims to determine the level of effectiveness and contribution of PKB and BBNKB to Aceh’s local own revenues. This type of research is a descriptive qualitative research. The data used in this research are primary data obtained from interviews and secondary data obtained by the documentation method, these data were obtained from Badan Pengelolaan Keuangan Aceh (BPKA). The results of this research indicate that the level of effectiveness of the PKB in Aceh for the 2015-2019 period has reached the very effective criteria with an average percentage of 103.76% and BBNKB is still included the quite effective criteria with an average percentage of 91.84%. The level of PKB's contribution to the Aceh’s local own revenues for the 2015-2019 period is still included the less criteria with an average percentage of 16.26%, as well as BBNKB with an average percentage of 15.28%.